Quantitation of Imidazoles by Agar-Disk Diffusion - Grendahl, Jan G. (1978)
A simple, reliable, and inexpensive assay for quantitation of the imidazole drugs miconazole, RV 40,500, and RV 41,400 was tested. The assay, similar to a Kirby-Bauer test, was sensitive to less than or equal to 0.2 μg of drug per ml and linear from less than or equal to 0.2 to 10.0 μg/ml. Concentration of inoculum and agar depth in test plates was not as critical as the type of medium, amount of inoculum, or type of drug used.